JOKO OR JOHN: NAME AND IDENTITY OF ENGLISH TUTORS IN KAMPUNG INGGRIS, PARE, INDONESIA - Tusita, Arcci (International Journal of Research -GRANTHAALAYAH, 2020)
Since name is one factor which shapes a person’s sense of identity, the exploration of the choice of names can shed a light to self-boundaries and identity. Thus, this study aims to show connection between Western names chosen and used by English tutors in Kampung Inggris and their feeling of identity and self. Drawing on data collected from English tutors in Kampung Inggris, Pare, ethnography is applied as its method. Observation and random interview are done to help gathering the data. The findings show the important role of the choice of using Western names in shaping their identity reflected from the desired image to be displayed to others. First, they see Western names as a symbol of modernity and thus give them the sense of being modern and part of global citizen; second, English names used as strategy management to present themselves as ‘competent’ English tutor.